"Nothing to be ashamed of" or "Nagging"? The Interaction Effects of Service Type and Failure Attributions on Satisfaction with Service Remediation - Zhao, Zeyu; Zou, Xingye; Xu, Haoran (International Theory and Practice in Humanities and Social Sciences, 2025)
With the development of Internet technology, more and more transaction scenarios are realised through the Internet, but how service failures are remediated on line born with it has raised concerns. Current research on how service type and failure attribution affect service remediation satisfaction through processing fluency and consumer perceived behavioural control is relatively weak, and this paper analyses the mechanisms in depth through three experiments. It is found that service type and failure attribution have a matching effect, in which intelligent customer service is more suitable for resolving objective failures and manual customer service is more suitable for resolving subjective failures; processing fluency and perceived behavioural control play a dual mediating role; and remediation strategy plays a moderating role in the main effect. This study not only enriches the research on the influence mechanism of service remediation satisfaction, but also has a better guidance on how enterprises can choose different types of customer service and remediation strategies under different attributed service failure scenarios.